Евалуација на когнитивните функции по разни видови анестезија - Трајкова, Радмила (Медицински факултет, УКИМ, Скопје, 2017)
Modern anesthesiology widens the existing knowledge of consciousness and memory of humans in a unique way by using anesthetics, which in different doses cause different changes in the consciousness of the patient, from amnesia to unconsciousness. Cognitive function is defined as the capability to fulfill the basic psychological capacities such as, perception, memory, reasoning, acquired skills (writing and reading) and using them to adapt to the conditions of the social environment. New clinical studies recognize loss or decrease of cognitive function as a complication of anesthesia and surgical intervention. Existing research has particularly targeted the effects in elderly patients going through non – cardiac surgical interventions. Goal: The main goal of this paper is to analyze the influence of anesthesia and its varieties to the incidence of postoperative cognitive dysfunction, to analyze the age of the patient as a determinant of cognitive dysfunction, as well as all the other preoperative and postoperative variables that can influence the cognitive status of the patients older than sixty years. Data and method: This paper is a retrospective/prospective study which analyzes 100 patients under anesthesia aged 60 to 86 admitted to the hospital GOB “8mi Septemvri” for surgical intervention in digestive surgery, urology surgery and orthopedic surgery. The field research was conducted in the department for anesthesia, reanimation and intensive care (DARIC). After receiving formal consent from the patients to be included in the study they were randomly assigned in either general endotracheal anesthesia (GEA) or regional anesthesia (RA). All patients included in the study underwent tests for pre-surgical assessment and classification of physical health (АСА - American Society of Anesthesiologists) and after the intervention patients were asked to assess the intensity of their post-operative pain using the scale for self-assessment of pain (VAS). The patients’ vital signs were carefully monitored pre, during and after the surgery. The evaluation of the mental status of the patients was conducted at four time points (pre-surgery t1, first post-surgery day t2, second post-surgery day t3, and seventh post-surgery day t4) at each time point the following tools were used: modified Blessed scale for orientation, memory and concentration (BOMC), and scale for simple diagnosis of delirium in non-psychiatric treatment (Confusion Assessment Method - CAM). Results: After the statistical analysis, the results were analyzed on the socio-demographic and clinical characteristic of the patients, the influence of the type of anesthesia, type of surgery and the changes in the patients’ post-operative cognitive status. Data received from the field study is visually presented in appropriate tables and charts while the correlations between the observed parameters were statistically tested. The study shows that 17% of elderly patients exhibit changes in their cognitive functions after being under anesthesia and undergoing a non-cardiac surgical intervention. The study found that the type of anesthesia is not a significant factor for determining the chances for post-operative cognitive dysfunction, furthermore regular cognitive function was restored by the seventh day after the surgery in most patients. A significant correlation was found between the age of the patient and the overall score on the Blessed scale as a predictor for experiencing post-operative cognitive dysfunction. The length of the surgery and the level of pain the patient experiences after the surgery have also been found to be related to the chance of the patient experiencing post-operative cognitive dysfunction. Conclusion: To prevent and treat cognitive dysfunction a multidisciplinary approach needs to be employed. This study suggests implementing diagnostic questionnaires as screening tools in the admittance process for evaluating the possibility of the patient experiencing postoperative cognitive dysfunction. In this way we will actively contribute to lowering the incidence of cognitive dysfunction, reducing the patient’s stay in hospitals and all around improving the quality of life of elder patients after non cardiac surgery.
Evaluation of cognitive functions after different types of anesthesia
Докторска дисертација одбранета во 2017 година на Медицинскиот факултет во Скопје, под менторство на проф. д–р Марија Шољакова.
Keywords: anesthesia, postoperative cognitive dysfunctions, non-cardiac surgery